O36-3 A case-crossover study of heat exposure and injury risk in agricultural workers in washington state, USA. (1st September 2016) - Spector, June
Abstract : Introduction: Occupational heat exposure has been reported to be associated with increased injury risk in certain populations. The objective of this study was to evaluate the association between heat exposure and occupational injury risk in Washington, USA outdoor agricultural workers. Methods: A case-crossover study using time-stratified referent selection was conducted among 12, 213 outdoor agricultural workers with new Washington (WA) State Fund workers' compensation traumatic injury claims from 2000–2012. Maximum daily Humidex exposures were derived from University of Washington Climate Impacts Group gridded meteorological data. Latitude and longitude of injury locations were assigned using US Census TIGER/Line 2014 reference data and joined with exposure data using a Euclidean nearest neighbour approach. Exposure levels were categorised a priori using an adapted version of the Occupational Health Clinics for Ontario Workers scheme. Odds ratios of injury risk for daily maximum Humidex categories were estimated using conditional logistic regression. Results: The mean of within stratum (injury day and corresponding referent days) standard deviations of daily maximum Humidex was 4.6°C (mean number of referent days per injury day 3.2). Compared to the reference category of <25°C daily maximum Humidex, odds ratios and 95% confidence intervals of injury were 1.14 (1.07–1.23) at 25–29°C, 1.18 (1.09–1.29) at 30–33°C, and 1.14 (1.04–1.25) at 34°C or greater, adjusting for job tenure. Conclusions: An increased risk of WA workers' compensation injuries in warm conditions was observed in outdoor agricultural workers. Similar findings were observed in sensitivity analyses and with stratification by job duty. Prevention efforts should focus on reducing injury risk in workers labouring in warm conditions, with the aim of minimising adverse heath effects of occupational heat exposure, which extend beyond heat-related illness to include injuries.